A literature review on commitment among quantity surveyors - Mohd Tarmizi, Nur Atikah; Mohyin, Nur Affah (2012)
This paper reports a literature review on commitment among quantity surveyors in Malaysia. The review aims to discover the meanings of commitment held by male and female quantity surveyor employees through the exploration of meanings of commitment done from previous studies. Additionally, the study seeks the factors lead to commitment among quantity surveyors by reviewing the commitment antecedents and its consequences to the employees together with an overview of commitment in construction industry.